Gas Bubble Dynamics During Methane Hydrate Formation and its Influence on Geophysical Properties of Sediment Using High-Resolution Synchrotron Imaging and Rock Physics Modeling - Madhusudhan, B. N.; Sahoo, S. K.; Alvarez-Borges, F.; Ahmed, S.; North, L. J.; Best, A. I. (Frontiers in Earth Science, 2022)
Gas bubble in aquatic sediments has a significant effect on its geophysical and geomechanical properties. Recent studies have shown that methane gas and hydrate can coexist in gas hydrate–bearing sediments. Accurate calibration and understanding of the fundamental processes regarding such coexisting gas bubble dynamics is essential for geophysical characterization and hazard mitigation. We conducted high-resolution synchrotron imaging of methane hydrate formation from methane gas in water-saturated sand. While previous hydrate synchrotron imaging has focused on hydrate evolution, here we focus on the gas bubble dynamics. We used a novel semantic segmentation technique based on convolutional neural networks to observe bubble dynamics before and during hydrate formation. Our results show that bubbles change shape and size even before hydrate formation. Hydrate forms on the outer surface of the bubbles, leading to reduction in bubble size, connectivity of bubbles, and the development of nano-to micro-sized bubbles. Interestingly, methane gas bubble size does not monotonously decrease with hydrate formation; rather, we observe some bubbles being completely used up during hydrate formation, while bubbles originate from hydrates in other parts. This indicates the dynamic nature of gas and hydrate formation. We also used an effective medium model including gas bubble resonance effects to study how these bubble sizes affect the geophysical properties. Gas bubble resonance modeling for field or experimental data generally considers an average or equivalent bubble size. We use synchrotron imaging data to extract individual gas bubble volumes and equivalent spherical radii from the segmented images and implement this into the rock physics model. Our modeling results show that using actual bubble size distribution has a different effect on the geophysical properties compared to the using mean and median bubble size distributions. Our imaging and modeling studies show that the existence of these small gas bubbles of a specific size range, compared to a bigger bubble of equivalent volume, may give rise to significant uncertainties in the geophysical inversion of gas quantification.